Amyloid Beta1–42 and the Phoshorylated Tau Threonine 231 in Brains of Aged Cynomolgus Monkeys (Macaca fascicularis) - Darusman, Huda Shalahudin; Gjedde, Albert; Sajuthi, Dondin; Schapiro, Steven J.; Kalliokoski, Otto; Kristianingrum, Yuli P.; Handaryani, Ekowati; Hau, Jann (Frontiers in Aging Neuroscience, 2014)
Pathological hallmarks indicative of Alzheimer’s disease, which are the plaques of Amyloid Beta 1-42 and neurofibrillary tangles, were found in brain of aged cynomolgus monkey. The aim of the study was to investigate if aged monkeys exhibiting spatial memory impairment and levels of biomarkers indicative of Alzheimer’s disease, had brain lesions similar to human patients suffering from senile dementia. Generating immunohistochemistry technique to biomarkers of Amyloid beta 1-42 and the phosphorylated tau 231, our study assessed the amyloidopathy, such as indicative to the senile plaques and cerebral amyloid angiopathy, and the tauopathy, to possible neurofibrillary tangles. Six aged monkeys were selected based on their spatial memory performance and profile of biomarkers of Alzheimer’s disease, divided equally to affected aged subject - with Memory-affected and low amyloid level, and aged with higher performance in memory and amyloid, as the age-matched subjects. Using immunohistochemistry, plaques of Amyloid Beta 1-42 were observed in two out of three brains of aged subjects with memory impairment and biomarkers indicative of Alzheimer’s disease. The cerebral amyloid angiopathy was observed in both aged monkey groups, and unlike in the human, the amyloids were found to deposit in the small veins and capillaries. In one of the affected individuals, phosphorylated tau was positively stained intracellularly of the neurons, indicating a possibility of an early stage of the formation of tangles. These findings add to the body of evidence of the utility of the aged cynomolgus monkeys as a spontaneous model for Alzheimer-related disease.